Pelatihan Pembuatan Sabun Alami Berbasis Ecoenzyme di Pesantren Nurul Huda Kabupaten Cianjur - Alpiyasin, Feri; Paujiah, Epa; Hartati, Sri; Fauzia, Eva Latifah (GEN ID, 2025)
As part of community empowerment efforts and the promotion of environmental literacy among Islamic boarding school students (santri), this community service activity aimed to provide training on the production of ecoenzymes from domestic waste as an environmentally friendly and economically valuable waste management solution. The training was conducted in the form of an integrated workshop that included hands-on practice in making ecoenzymes, producing eco-friendly soap, product packaging, and digital marketing training. The results of the activity showed an increase in participants’ knowledge and skills in utilizing waste into useful products with entrepreneurial potential. This was measured by indicators such as the ability to explain the concept and steps of product making, as well as the ability to practice them—evaluated through direct Q&A with participants after the training. This initiative marked the beginning of building a self-sufficient, productive, and environmentally conscious pesantren ecosystem.